Digital Accounting and Blockchain: Transforming Financial Record-Keeping in the Era of Decentralization - Muhammad Hasyim Ashari (Oikonomia : Journal of Management Economics and Accounting, 2026)
The convergence of digital accounting and blockchain technology represents one of the most consequential transformations in contemporary financial management. This study conducts a systematic literature review to examine how blockchain technology reshapes financial record-keeping, transparency, auditability, and accountability in the era of decentralization. Drawing from 25 peer-reviewed publications spanning 2021 to 2026, this research synthesizes empirical findings and theoretical frameworks concerning the adoption, implementation, and outcomes of blockchain-based accounting systems. The review identifies four principal dimensions of transformation: (1) immutable ledger infrastructure that eliminates retrospective manipulation of financial data; (2) smart contract automation that reduces human error and accelerates financial closing cycles; (3) distributed ledger technology (DLT) integration with enterprise resource planning (ERP) and accounting information systems (AIS); and (4) real-time financial reporting that enhances stakeholder decision-making. This paper further explores persistent challenges, including regulatory ambiguity, interoperability limitations, energy consumption concerns, and the skills gap among accounting professionals. The novelty of this study lies in its integration of ESG reporting dimensions and decentralized governance implications into the blockchain-accounting nexus, areas insufficiently addressed in prior reviews. Findings indicate that blockchain adoption can reduce financial fraud, improve audit efficiency by up to 40%, and enable continuous real-time reporting, fundamentally altering the role of the accountant in a digitally decentralized economy.